Evaluation of the effectiveness of maternal immunization against pertussis in Alberta using agent-based modeling: A Canadian immunization research network study. Issue 15 (6th April 2023) - Hempel, Karsten; McDonald, Wade; Osgood, Nathaniel D.; Fisman, David; Halperin, Scott A.; Crowcroft, Natasha; Klein, Nicola P.; Rohani, Pejman; Doroshenko, Alexander
Highlights: Vaccination of pregnant women is recommended to reduce pertussis in infants. A novel agent-based mathematical model was developed to examine several phenomena. Maternal vaccination results in reduction in future pertussis cases in infants. Immunological blunting has moderate effect on maternal vaccination effectiveness. Interruption of exposure pathways reduces pertussis disease in infants. Abstract: Introduction : The re-emergence of pertussis has occurred in the past two decades in developed countries. The highest morbidity and mortality is seen among infants. Vaccination in pregnancy is recommended to reduce the pertussis burden in infants. Methods : We developed and validated an agent-based model to characterize pertussis epidemiology in Alberta. We computed programmatic effectiveness of pertussis vaccination during pregnancy (PVE) in relation to maternal vaccine coverage and pertussis disease reporting thresholds. We estimated the population preventable fraction (PFP) of different levels of maternal vaccine coverage against counterfactual "no-vaccination" scenario. We modeled the effect of immunological blunting and measured protection through interruption of exposure pathways. Results : PVE was inversely related to duration of passive immunity from maternal immunization across most simulations. In the scenario of 50% maternal vaccine coverage, PVE was 87% (95% quantiles 82–91%), with PFP of 44% (95% quantiles 41–45%). For monthly age intervals of 0–2, 2–4, 4–6 and 6–12, PVE ranged between 82 and 99%, and PFP ranged between 41 and 49%. At 75% maternal vaccine coverage, PVE and PFP were 90% (95% quantiles 86–92%) and 68% (95% quantiles 65–69%), respectively. At 50% maternal vaccine coverage and 10% blunting, PVE and PFP were 86% (95% quantiles 77–87%) and 43% (95% quantiles 39–44%), respectively, while at 50% blunting, the corresponding values of PVE and PFP were 76% (95% quantiles 70–81%) and 38% (95% quantiles 35–40%). PVE attributable to interruption of exposure pathways was 54–57%. Conclusions : Our model predicts significant reduction in future pertussis cases in infants due to maternal vaccination, with immunological blunting slightly moderating its effectiveness. The model is most sensitive to maternal vaccination coverage. The interruption of exposure pathways plays a role in the reduction of pertussis burden in infants due to maternal immunization. The effect of maternal immunization on population other than infants remains to be elucidated.